Prevalence,Isolation Techniques, Antibiotic Pattern and Plasmid Profile of Salmonella in Broiler Chicken During Production, Processing and Retail Outlets - Hashim, Jamal Khair (1998)
Five hundred and forty nine (549) of carcasses and intestinals content and 73 samples of chicken litter and feed were examined for Salmonella. Two hundred and thirty (237) Salmonella isolates belonging to 15 different serotypes were isolated. The predominant serotypes were: S. enteritidis (35.2%), S. muenchen (20%), S. kentucky (14.3%), S. blockley (10.4%) and S. chincol (5.2%). S. enteritidis were detected throughout the broiler production chain. The detection rate of Salmonella in poultry carcasses under different conditions were as follows: 83% (126/232), direct enrichment of pelleted (DEP) rinse fluid In Rapaport Vasiliadis broth (RV) incubated at 42°C; 28% (43/232) ,for both DEP enriched in RV and Manitol Selanite Cystine Broth (MSCB) incubated at 37°C; and 9% (14/232), streaking the pellet directly onto the plating media. In a parallel analysis, the conventional method detected Salmonella in 43.5% (115/264) of carcasses, litter and feed samples compared to 18.2% (48/264) detected by rapid method TECRA UNIQUE Salmonella test kit. Two hundrad and thirty seven (237) isolates of Salmonella belonging to 15 different serovars were susceptible to gentamicin, advosin and enrofloxacin except for one isolate of S. agona, which was resistant to enrofloxacin. S. kentucky isolates displayed 11 discrete antibiotic resistant patterns, followed by S. blockley (7), s. agona (4) and S. muenchen (3). Plasmids were detected in 80% of the isolates with molecular weights ranging from <1 to 50 MDa. The frequency of plasmids in different serovars are as follows: S. blockely (96%), S. chnicol (92%), s. muenchen (90%); S. kentuckey (88%) and S. enteritidis (75%). Different variations in plasmid profile pattern were exhibited by S. muenchen (24 patterns), S. kentucky (11 patterns), S. blockley (14 patterns), S. enteritidis (7 patterns), S. chincol (4 patterns) and S. newport (5 patterns).